Pre- and Post-Pandemic Curriculum Needs: A Constructivist Perspective - Kurniawan, Syamsul; Maimunah (Universitas Negeri Yogyakarta, 2025)
Change is an inevitability in education, where the curriculum must serve as a dynamic roadmap guiding learners to construct knowledge actively and independently. This article examines the evolving needs of Indonesia’s educational curriculum before and after the Covid-19 pandemic through the lens of constructivism, a learning philosophy that positions students as active knowledge constructors. Employing a qualitative approach grounded in literature review and descriptive analysis, the study explores how the 2013 Curriculum, the Emergency Curriculum, and the Merdeka Curriculum have responded to shifting pedagogical demands in both face-to-face and remote learning contexts. Findings indicate that the pandemic accelerated a paradigm shift toward more flexible, student-centered, and project-based curriculum models. However, the primary challenges remain in the uneven readiness of educators and disparities in technological infrastructure. The significance of this study lies in its contribution to reinforcing the philosophical foundation for the development of adaptive curricula aligned with future educational demands. It also offers strategic recommendations for policymakers and educational practitioners. Furthermore, the study opens avenues for future research on the practical implementation of constructivist curricula across diverse settings, including teacher capacity-building and the evaluation of project-based learning effectiveness within the Merdeka Curriculum framework.